PREDICTIVE ANALYTICS OF HEALTHCARE DATA - Waghmare, Apurva; Hemalatha, Sweetlin (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Predictive analytics is employed to improve the ability to take precautionary measures during medical emergencies. In health care, the sensor-based data are generated daily which can be used to predict future data using regression model. In this paper, pain dataset from integrating data for analysis, anonimyzation, and sharing repository is used for experimenting different machine algorithms. The results show that logistic regression gives more accuracy than other algorithms.